BILINGUALISM AS A LINGUISTIC AND COGNITIVE PHENOMENON: A COMPARATIVE AND FUNCTIONAL PERSPECTIVE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This paper explores bilingualism as a complex linguistic, cognitive, and sociocultural phenomenon in the context of modern linguistics. In an increasingly globalized world, bilingualism has become a widespread and socially significant condition, influencing language development, identity formation, and intercultural communication. The study examines the main types of bilingualism, its cognitive and linguistic implications, and its role in literary and social discourse.